Side effects of traditional pesticides on soil microbial respiration in orchards on the Russian Black Sea coast. (July 2021) - Karpun, Natalia N.; Yanushevskaya, Eleonora B.; Mikhailova, Yelena V.; Díaz-Torrijo, Javiera; Krutyakov, Yurii A.; Gusev, Alexander A.; Neaman, Alexander
Abstract: Agricultural use of pesticides has greatly increased worldwide over the last several decades, affecting soil microorganisms. Microbial basal respiration and substrate-induced respiration rates are commonly used to assess the detrimental effects of pesticides on soil quality. The goal of the present study was (1) to compare the impact of different pesticides on soil microbial respiration under field conditions, and (2) to characterize the recovery time of soil microbial respiration after pesticide application. The following pesticides were used in the present study: chlorpyrifos, phosalone, dimethoate (organophosphorus insecticides), λ-cyhalothrin (pyrethroid insecticide), and kresoxim-methyl (fungicide). The application of all the pesticides at commercial doses led to a decrease in soil microbial respiration. The inhibition of basal respiration and substrate-induced respiration rate decreased in the following order: chlorpyrifos > phosalone > dimethoate > λ-cyhalothrin ≈ kresoxim-methyl. Among all the pesticides assessed, chlorpyrifos showed the highest toxicity as well as the highest persistence. Several of the observed results differed greatly from previous studies; thus, local assessments are highly advisable. Given that environmental concerns can be a key decision factor for pesticide selection, assessment of different pesticides—such as undertaken in this study—could help farmers to choose the most appropriate pesticide. Highlights: Pesticides at commercial doses led to a decrease in soil microbial respiration. Chlorpyrifos showed the highest toxicity as well as the highest persistence. Local assessments of pesticides are highly advisable. Pesticide assessment help farmers to choose the most appropriate pesticide.